Drug war pathologies : embedded corporatism and U.S. drug enforcement in the Americas - Bartilow, Horace A. (University of North Carolina Press, 2019)
"In this book, Horace Bartilow develops a theory of embedded corporatism to explain the U.S. government's war on drugs. Stemming from President Richard Nixon's 1971 call for an international approach to this 'war, ' the U.S. drug enforcement policy has persisted to the present day, despite widespread criticism of its effectiveness and of its unequal effects on hundreds of millions of people across the Americas. While research has consistently emphasized the role of race in U.S. drug enforcement, Bartilow's analysis empirically highlights the class dimension of the drug war and the immense power that American corporations wield within the regime. Drawing on qualitative case study methods, declassified U.S. government documents, and advanced econometric estimators that analyze cross-national data, Bartilow systematically demonstrates how corporate power, as projected through corporate lobbies, corporate financing of federal elections, corporate funding of policy think tanks, and corporate interlocks with the federal government and the military, create the conditions in which the divergent interests of state and nonstate members of the regime converge in ways that promote capital accumulation. The subsequent human rights repression, illiberal democratic governments, repression of workers, and widening income inequality throughout the Americas, Bartilow argues, are the pathological policy outcomes of the embedded corporatist drug enforcement regime"--